Helping Callers to the National Suicide Prevention Lifeline Who Are at Imminent Risk of Suicide: Evaluation of Caller Risk Profiles and Interventions Implemented. Issue 2 (4th August 2015) - Gould, Madelyn S.; Lake, Alison M.; Munfakh, Jimmie Lou; Galfalvy, Hanga; Kleinman, Marjorie; Williams, Caitlin; Glass, Andrew; McKeon, Richard
Abstract : Crisis lines are settings where identifying individuals at imminent risk of suicidal behavior and intervening to keep them safe are critical activities. We examined clinical characteristics of crisis callers assessed by telephone crisis helpers as being at imminent risk of suicide, and the interventions implemented with these callers. Data were derived from 491 call reports completed by 132 helpers at eight crisis centers in the National Suicide Prevention Lifeline network. Helpers actively engaged the callers in collaborating to keep themselves safe on 76.4% of calls and sent emergency services without the callers' collaboration on 24.6% of calls. Four different profiles of imminent risk calls emerged. Caller profiles and some helper characteristics were associated with intervention type. Our findings provide a first step toward an empirical formulation of imminent risk warning signs and recommended interventions.